Do College Social Justice Activists Stop When They Graduate? Explaining Volunteer Activist Participation in a Life Course Transition. (9th March 2021) - Horowitz, Jonathan
Abstract: Why does volunteer participation by college social justice activists decline dramatically following graduation? Using a new, multimethod longitudinal study that spans college and the early post-graduate years, I test existing theory about how changes in time constraints, social support, and organizational opportunities affect volunteer activist participation in social justice movements. Analyzing qualitative data from semi-structured interviews to further understand decreases in activism, I find no evidence showing that changes in time constraints or social support lead to changes in activist volunteering, but there is evidence to support the effects of organizational opportunities. Findings from the qualitative data further emphasize that activist opportunities are easier to access on college campuses, specifically because activism is physically convenient to the potential participant. Future research and practice should explicitly address the spatial proximity of potential activists to social movement opportunities, and should additionally remain sensitive to different needs of activists at different points in the life course.